Breaking Through Binarities: Islamic Education in the Vortex of Gender, Sexuality, and Human Rights - Husni Husni; Walter Hayden; Didih Syakir Munandar; Muhamad Aris Munawar (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The issue of gender binary, sexuality, and human rights in Islamic education discourse in Indonesia is an area that is often neglected but crucial for the relevance of religious education in the contemporary era. Aiming to analyze the understanding of PAI teachers, school principals, and students regarding these issues and how PAI reflects or responds to them, this study identifies challenges and opportunities in integrating non-binary perspectives. Using a qualitative approach with a multiple case study design at SMAN 1 and SMAN 2 in Ciamis District, data were collected through in-depth interviews with four PAI teachers, two school principals, and several students, supplemented by document analysis. The research indicates that the majority of PAI teachers and school leaders also retain a binary understanding of gender and sexuality. Many of these teachers also report feeling inadequately prepared or unable to know where to start when it comes to teaching these issues. Although there is a general commitment to human rights, its implementation in these sensitive issues remains limited. On the other hand, students demonstrate ambiguity, accepting the binary narrative of PAI while also being exposed to diversity from other sources, creating a gap between formal teachings and their lived realities. As a result, PAI risks losing relevance and creating an environment that is less inclusive if it does not adapt to broader socio-cultural realities. This requires curriculum development, teacher training, and more progressive school policies to foster a more comprehensive understanding of religion, humanity, and diversity.